Figurative Language in ‘Red’ Song Lyrics by Taylor Swift - Ria Yuliasari; Rika Virtianti (Pujangga: Jurnal Bahasa dan Sastra, 2023)
ABSTRACT Song is an artistic expression of feelings, ideas or thoughts. Sometimes the lyrics of a song are easy to understand, but sometimes the lyrics are so poetic that they are difficult to understand. .This research aims at analyzing figurative language found in the song lyrics of ‘Red’ by Taylor Swift. The method used in this research is descriptive qualitative to analyze the types of figurative language found in the song lyrics and also the meaning of the figurative language. The analysis of the types of simile expressions is carried out using theory of Perrine and Rozakis. The result of the analysis shows that ‘Red’ song lyrics has eighteen figurative languages that belong to the type of simile, symbol, metaphor and hyperbole.  Keywords: figurative language, song, lyrics.